Bimetal composite oxide modified ceramic membrane as well as preparation method and application thereof

By forming a bimetal composite oxide layer on the ceramic membrane, the problem of easy clogging of the ceramic membrane is solved, the anti-pollution performance and filtration efficiency are improved, the service life is extended and the production cost is reduced.

CN119588176AActive Publication Date: 2025-03-11SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411699613.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing ceramic membranes are prone to clogging, resulting in a decrease in membrane flux, blockage of membrane pores and an increase in transmembrane pressure difference. In turn, it is necessary to increase the physical backwash frequency and chemical cleaning frequency, increasing energy consumption and operating costs.

Method used

Using the preparation method of bimetallic composite oxide modified ceramic film, a ceramic film support is prepared by calculating materials such as alumina powder through gradient heating, and then depositing metal salts such as magnesium nitrate and manganese nitrate on its surface to form a bimetallic composite oxide layer that catalyzes ozone properties.

Benefits of technology

It improves the anti-pollution performance and filtration efficiency of ceramic membranes, extends service life, reduces production costs, and solves the problem of difficulty in recycling powder catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a bimetallic composite oxide modified ceramic membrane as well as a preparation method and application thereof, and belongs to the technical field of ceramic membranes. According to the invention, industrial-grade aluminum oxide is used as a raw material, and the binder, the pore-forming agent, the fluxing agent, the anti-shrinking agent and the like are added, so that the roasting temperature of the ceramic membrane support is reduced, and the manufacturing cost of the ceramic membrane is reduced; by constructing a bimetallic oxide composite coating with a catalytic ozonation function on the surface of the ceramic membrane, oxidative degradation of organic pollutants on the surface of the ceramic membrane is realized, so that the anti-pollution performance of the ceramic membrane is improved, and the service life of the ceramic membrane is prolonged. The problems that an existing ceramic membrane is high in manufacturing cost and prone to membrane pollution are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic membranes, and in particular relates to a bimetallic composite oxide modified ceramic membrane and a preparation method and application thereof. Background Art

[0002] Ceramic membrane is a common inorganic membrane separation material, which is mainly prepared by ceramic raw materials such as TiO2, ZrO2, Al2O3 and SiO2 through a specific process and has a multi-level pore structure. Compared with organic membranes, ceramic membranes have the advantages of high temperature and high pressure resistance, high mechanical strength, good chemical stability, long service life and easy cleaning. They have been successfully used in water treatment fields such as drinking water purification, natural organic matter removal, municipal sewage treatment, industrial wastewater reuse and seawater desalination.

[0003] The production of ceramic membranes involves complex manufacturing processes, including powder preparation, molding, sintering and other steps, as well as the addition of additives such as pore formers, binders, co-solvents, and anti-shrinkage agents. In addition, ceramic membranes are brittle and fragile, which is inconvenient during transportation, installation and use, which increases the cost of using ceramic membranes.

[0004] In addition to the high production cost, during the ceramic membrane treatment of wastewater, pollutants in the wastewater will inevitably deposit on its surface under the action of polar force, electrostatic attraction, van der Waals force, concentration polarization, etc., forming a dense pollution layer or blocking the membrane pores, causing a decrease in membrane flux, blockage of membrane pores and an increase in transmembrane pressure difference, which requires an increase in the frequency of physical backwashing and chemical cleaning. Excessive cleaning frequency will not only bring a lot of additional energy consumption and membrane cleaning wastewater, but also lead to a decrease in membrane performance, a shortened lifespan and an increase in operating costs. Therefore, solving the problem of ceramic membrane pollution is of great practical significance for expanding the application of ceramic membranes. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a bimetallic composite oxide modified ceramic membrane and a preparation method and application thereof, so as to solve the technical problem that the existing ceramic membrane is easily blocked.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is to provide a method for preparing a bimetallic composite oxide modified ceramic membrane, comprising the following steps: S1: Alumina powder, a binder, a pore-forming agent, a flux and an anti-shrinkage agent are mixed, and then the mixture is pressed into a ceramic membrane embryo, and then the ceramic membrane embryo is subjected to gradient temperature rise calcination to obtain a ceramic membrane support body; the gradient temperature rise calcination is: firstly heating to 900°C at a heating rate of 5°C / min, keeping warm for 30min, then heating to 1200°C at a heating rate of 2°C / min, keeping warm for 30min, then heating to 1400-1600°C at a heating rate of 1°C / min, and keeping warm for calcination for 2h; or firstly heating to 900°C at a heating rate of 5°C / min, keeping warm for 30min, then heating to 1150°C at a heating rate of 2°C / min, and keeping warm for calcination for 2h; S2: dissolving metal salt, urea and polyvinyl pyrrolidone in water to obtain a mixed solution; the metal salt is a mixture of magnesium nitrate and manganese nitrate; S3: Place the ceramic membrane support in the mixed solution, immerse for 4 hours, then bake at 60-120° C. for 4 hours, and then dry and calcine to obtain a bimetallic composite oxide modified ceramic membrane.

[0007] Based on the above technical solution, the present invention can also be improved as follows.

[0008] Furthermore, the mass fraction of the binder in the mixture is 0.5-3%, the mass fraction of the pore former is 0.05-0.5%, the mass fraction of the flux is 0.5-10%, and the mass fraction of the anti-shrinkage agent is 0.5%.

[0009] Furthermore, the binder is carboxymethyl cellulose, polyvinyl alcohol or polyvinyl pyrrolidone; the pore-forming agent is ammonium chloride, starch or sodium alginate; the flux is boric acid, calcium oxide or aluminum phosphate; and the anti-shrinkage agent is sodium carbonate.

[0010] Furthermore, the pressure when the mixture was pressed in S1 was 20t.

[0011] Furthermore, the mass ratio of magnesium nitrate to manganese nitrate in the metal salt is 2:1.

[0012] Furthermore, the molar ratio of urea to metal salt in the mixed solution is 3-6:1.

[0013] Furthermore, the concentration of urea in the mixed solution is 0.33 mol / L; the concentration of polyvinyl pyrrolidone is 10 g / L.

[0014] Furthermore, in S4, the drying is performed at 105° C. for 2 h; and the calcination is performed at 550° C. for 2 h.

[0015] The invention also discloses a bimetallic composite oxide modified ceramic membrane prepared by the preparation method.

[0016] The invention also discloses the application of the bimetallic composite oxide modified ceramic membrane in bovine serum albumin filtration or catalytic ozonation treatment of bovine serum albumin.

[0017] The beneficial effects of the present invention are: 1. The present invention selects low-priced and easily available industrial-grade alumina and optimizes the material formula to obtain a homemade ceramic membrane with high strength and good filtration performance, and gives the ceramic membrane catalytic ozone performance, thereby improving the membrane's anti-pollution performance, increasing its service life, and reducing the production cost of the ceramic membrane.

[0018] 2. The present invention uses transition metal manganese and alkaline earth metal magnesium as a control strategy, which can increase the number of acidic sites and alkaline sites on the surface of the ceramic membrane, thereby improving the catalytic ozonation efficiency of the ceramic membrane, and further enhancing the filtration efficiency of the catalytic ceramic membrane.

[0019] 3. In-situ coupling of the ceramic membrane with catalytic ozone not only solves the problem of difficulty in recovering powdered catalysts, but also further improves the anti-pollution ability of the ceramic membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The SEM characterization results of the bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1; Figure 2 The membrane pore analysis diagram of the bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1; Figure 3 The results of filtering bovine serum albumin by the bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1 are shown; Figure 4 This is a graph showing the results of in-situ coupled catalytic ozonation treatment of bovine serum albumin by the bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1. DETAILED DESCRIPTION

[0021] The specific implementation modes of the present invention are described in detail below with reference to the embodiments. Example 1

[0022] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: (1) Alumina powder, polyvinyl pyrrolidone (PVP), starch, boric acid and sodium carbonate are uniformly mixed to obtain a mixture, wherein the mass fractions of PVP, starch, boric acid and sodium carbonate in the obtained mixture are 1%, 0.1%, 5% and 0.5%, respectively, and the balance is alumina powder; then the mixture is transferred to a mold and pressed into a ceramic membrane embryo at a pressure of 20t; then the ceramic membrane embryo is placed in a muffle furnace, first heated to 900°C at a heating rate of 5°C / min, kept warm for 30min to remove organic matter, then heated to 1200°C at a heating rate of 2°C / min, kept warm for 30min, and finally heated to 1500°C at a heating rate of 1°C / min, and calcined for 2h to ceramicize the embryo to generate a ceramic membrane support with high strength and good stability; (2) Dissolve magnesium nitrate, manganese nitrate, urea and PVP in water to prepare a mixed solution, wherein the mass ratio of magnesium nitrate to manganese nitrate is 2:1, the molar ratio of urea to metal salt is 4.5:1, the concentration of urea is 0.33 mol / L; the concentration of PVP is 10 g / L; place the ceramic membrane support prepared in step (1) into the mixed solution, immerse for 4 hours, and then transfer to an oven, first bake at 80°C for 4 hours, and then dry at 105°C for 2 hours to obtain a modified ceramic membrane embryo, and finally calcine at 550°C for 2 hours to obtain a bimetallic composite oxide modified ceramic membrane, denoted as Mn-Mg / CM-H. Example 2

[0023] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The polyvinyl pyrrolidone (PVP) in step (1) was replaced by carboxymethyl cellulose, and the rest was the same as in Example 1. Example 3

[0024] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The polyvinyl pyrrolidone (PVP) in step (1) was replaced by polyvinyl alcohol, and the rest was the same as in Example 1. Example 4

[0025] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of polyvinyl pyrrolidone (PVP) in step (1) was adjusted to 0.5%, and the rest was the same as in Example 1. Example 5

[0026] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of polyvinyl pyrrolidone (PVP) in step (1) was adjusted to 1.5%, and the rest was the same as in Example 1. Example 6

[0027] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of polyvinylpyrrolidone (PVP) in step (1) was adjusted to 3%, and the rest was the same as in Example 1. Example 7

[0028] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The starch in step (1) was replaced by ammonium chloride, and the rest was the same as in Example 1. Example 8

[0029] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The starch in step (1) was replaced by sodium alginate, and the rest was the same as in Example 1. Example 9

[0030] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of starch in step (1) was adjusted to 0.05%, and the rest was the same as in Example 1. Example 10

[0031] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of starch in step (1) was adjusted to 0.3%, and the rest was the same as in Example 1. Embodiment 11

[0032] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of starch in step (1) was adjusted to 0.5%, and the rest was the same as in Example 1. Example 12

[0033] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The boric acid in step (1) was replaced by calcium oxide, and the rest was the same as in Example 1. Embodiment 13

[0034] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The boric acid in step (1) was replaced by aluminum phosphate, and the rest was the same as in Example 1. Embodiment 14

[0035] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of boric acid in step (1) was adjusted to 0.5%, and the rest was the same as in Example 1. Embodiment 15

[0036] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of boric acid in step (1) was adjusted to 3%, and the rest was the same as in Example 1. Example 16

[0037] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The mass fraction of boric acid in step (1) is adjusted to 10%, and the rest is the same as in Example 1. Embodiment 17

[0038] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: (1) Alumina powder, polyvinyl pyrrolidone (PVP), starch, boric acid and sodium carbonate are uniformly mixed to obtain a mixture, wherein the mass fractions of PVP, starch, boric acid and sodium carbonate in the obtained mixture are 1%, 0.1%, 5% and 0.5%, respectively, and the balance is alumina powder; then the mixture is transferred to a mold and pressed into a ceramic membrane embryo at a pressure of 20 tons; then the ceramic membrane embryo is placed in a muffle furnace, first heated to 900°C at a heating rate of 5°C / min, kept warm for 30 minutes to remove organic matter, then heated to 1100°C at a heating rate of 2°C / min, and calcined for 2 hours to ceramicize the embryo to generate a ceramic membrane support body with high strength and good stability; (2) Dissolving magnesium nitrate, manganese nitrate, urea and PVP in water to prepare a mixed solution, wherein the mass ratio of magnesium nitrate to manganese nitrate is 2:1, the molar ratio of urea to metal salt is 4.5:1, the concentration of urea is 0.33 mol / L, and the concentration of PVP is 10 g / L; placing the ceramic membrane support obtained in step (1) into the mixed solution, immersing for 4 hours, and then transferring to an oven, first baking at 80°C for 4 hours, and then drying at 105°C for 2 hours to obtain a modified ceramic membrane embryo, and finally calcining at 550°C for 2 hours to obtain a bimetallic composite oxide modified ceramic membrane. Embodiment 18

[0039] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The final calcination temperature in step (1) is adjusted to 1400° C., and the rest is the same as in Example 1. Embodiment 19

[0040] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The final calcination temperature in step (1) is adjusted to 1600° C., and the rest is the same as in Example 1. Embodiment 20

[0041] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The molar ratio of urea to metal salt in step (2) is adjusted to 3:1, and the rest is the same as in Example 1. Embodiment 21

[0042] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The molar ratio of urea to metal salt in step (2) is adjusted to 6:1, and the rest is the same as in Example 1. Embodiment 22

[0043] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The temperature of the baking reaction in step (2) was adjusted to 60° C., and the rest was the same as in Example 1. Embodiment 23

[0044] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The temperature of the baking reaction in step (2) was adjusted to 100° C., and the rest was the same as in Example 1. Embodiment 24

[0045] A bimetallic composite oxide modified ceramic membrane is prepared by the following steps: The temperature of the baking reaction in step (2) was adjusted to 100° C., and the rest was the same as in Example 1.

[0046] Comparative Example 1 A ceramic membrane is prepared by the following steps: Alumina powder, polyvinyl pyrrolidone (PVP), starch, boric acid and sodium carbonate were mixed evenly to obtain a mixture, in which the mass fractions of PVP, starch, boric acid and sodium carbonate were 1%, 0.1%, 5% and 0.5%, respectively, and the balance was alumina powder; the mixture was then transferred to a mold and pressed into a ceramic membrane embryo at a pressure of 20t; the ceramic membrane embryo was then placed in a muffle furnace, first heated to 900°C at a heating rate of 5°C / min, kept warm for 30min to remove organic matter, then heated to 1200°C at a heating rate of 2°C / min, kept warm for 30min, and finally heated to 1500°C at a heating rate of 1°C / min, and calcined for 2h to ceramicize the embryo to generate a ceramic membrane with high strength and good stability, which was recorded as CM-H.

[0047] Results Analysis The bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1 were characterized by SEM. Figure 1 As shown. Figure 1It can be seen that due to the use of industrial-grade alumina as raw material, alumina particles of different sizes accumulate to form pore structures of different sizes. Therefore, the selectivity of CM-H is poor, resulting in unstable membrane flux and retention rate during its filtration process. After the Mn-Mg metal oxide coating is used, the smaller Mn and Mg oxide particles are dispersed on the Al2O3 particles, repairing part of the pore structure and making the overall pore size of Mn-Mg / CM-H more uniform.

[0048] The bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1 were characterized by membrane pore analysis. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the pore size distribution of CM-H (220~400nm) is relatively wide, and the pore size distribution of Mn-Mg / CM-H membrane is 100nm; this indicates that the pore size distribution of the ceramic membrane is significantly more uniform after loading the active components (Mn, Mg oxide particles), and the active component coating repairs the pore defects of the original membrane. This may be because MnO x The particles are small and have good dispersibility. Generally speaking, the pore size of ceramic ultrafiltration membrane is 1~100nm, while the pore size of CM-H is larger and the selectivity for pollutants is lower. After modification by coprecipitation method, the pore structure of Mn-Mg / CM-H is improved and the selectivity is significantly improved. The results show that the ceramic membrane modified by the method of the present invention can effectively improve the filtration efficiency of the membrane itself.

[0049] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 2-3 were evaluated. The results are shown in Table 1.

[0050] Table 1 Binder type Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° PVP 140.3 17.54 0.266 46.04 Carboxymethyl cellulose 145.7 17.12 0.244 38.32 Polyvinyl alcohol 141.8 17.49 0.231 43.81 As can be seen from Table 1, there is no significant difference in the most probable pore size and linear shrinkage of the three binders. Carboxymethyl cellulose and polyvinyl alcohol are slightly better than PVP in improving hydrophilicity because the former are composed of a large number of carboxyl or hydroxyl groups. However, from the data of compressive strength, the compressive strength of the ceramic membrane support after using PVP is better than the other two. In addition, PVP's water solubility, thermal stability and other properties are better than the other two binders, making it easier and more feasible in the preparation process.

[0051] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 4 to 6 were evaluated. The results are shown in Table 2.

[0052] Table 2 PVP dosage Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 0.5% 116.8 17.19 0.214 60.34 1.0% 140.3 17.54 0.266 46.04 1.5% 149.8 17.19 0.273 27.88 3.0% 172.9 17.22 0.288 24.32 It can be seen from Table 2 that when the PVP addition is 0.5%, the pore size is mainly distributed between 100 and 120 nm, and the distribution is relatively uniform. As the amount of PVP increases, the pore size increases and the distribution becomes wider, indicating that PVP also has a pore-forming effect. The hydrophilicity test results show that as the amount of PVP increases, the water contact angle decreases and the hydrophilicity increases. It may be that the molecular structure of PVP contains a large number of acyl groups, which has a strong polarity and can form hydrogen bonds with water molecules, so its hydrophilicity is very strong. The amount of PVP has little effect on the linear shrinkage rate, but has a significant improvement on the strength of the support. When the amount of PVP increases from 0.5% to 1.0%, the compressive strength increases from 0.214 MPa to 0.266 MPa, but when it continues to increase to 1.5% (0.273 MPa) and 3.0% (0.288 MPa), the strength increase is not obvious, and a small amount of cracks will occur after sintering.

[0053] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 7-8 were evaluated. The results are shown in Table 3.

[0054] Table 3 Types of pore formers Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° starch 140.3 17.54 0.266 46.04 Ammonium chloride 155.7 19.20 0.219 38.32 Sodium alginate 131.8 16.31 0.275 36.31 As can be seen from Table 3, there is no significant difference in the performance of the three pore-forming agents for ceramic membrane supports. Sodium alginate is slightly better than the other two, but it is more expensive and the uniformity of the generated pores is more difficult to control. Ammonium chloride releases a small amount of gas during the calcination process, which has a certain impact on the strength of the support.

[0055] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 9 to 11 were evaluated. The results are shown in Table 4.

[0056] Table 4 Starch addition Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 0.05% 136.8 19.33 0.234 63.15 0.10% 140.3 17.54 0.266 46.04 0.30% 159.5 17.24 0.263 45.33 0.50% 162.9 16.51 0.270 44.29 It can be seen from Table 4 that when the starch addition is 0.05%, the compressive strength is low and the pore size distribution is uneven, which may be related to the dispersibility of starch. Increasing the amount of starch added makes the compressive strength and pore size distribution more uniform, but there is no obvious improvement if the amount of starch is further increased.

[0057] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 12 to 13 were evaluated. The results are shown in Table 5.

[0058] Table 5 Flux Type Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° Boric acid 140.3 17.54 0.266 46.04 Calcium Oxide 135.7 18.22 0.217 41.12 Sodium phosphate 133.6 17.31 0.232 43.71 It can be seen from Table 5 that the compressive strength of the ceramic membrane support prepared with boric acid as a flux is higher than that of the other two fluxes. This may be because boric acid can significantly reduce the temperature required for ceramicization during the sintering process of the support, and thus exhibits higher mechanical strength at the same calcination temperature.

[0059] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 14 to 16 were evaluated. The results are shown in Table 6.

[0060] Table 6 Boric acid dosage Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 0.5% 122.1 19.33 0.153 63.15 3.0% 153.1 22.11 0.173 51.27 5.0% 140.3 17.54 0.266 46.04 10.0% 313.2 12.14 0.134 46.29 As can be seen from Table 6, boric acid has little effect on the hydrophilicity of the support. Its average pore size shows a trend of first decreasing and then increasing with the increase of boric acid, indicating that the addition of an appropriate amount of boric acid can make the grain growth of the support more orderly, thus showing a more uniform pore structure. The compressive strength also shows the same rule. During the sintering process of the support, boric acid can form a thin film on the surface of the ceramic particles, enhance the bonding force between the ceramic particles, and thus improve the mechanical strength of the support. Therefore, as the amount of boric acid increases from 3% (0.173 MPa) to 5% (0.266 MPa), the strength of the support increases, but when it continues to increase to 10% (0.134 MPa), the mechanical strength decreases significantly. This may be because too much glass phase inhibits the growth of grains, resulting in uneven microstructure of the support and reduced mechanical strength.

[0061] The performance of the ceramic membrane CM-H prepared in Comparative Example 1 and the ceramic membrane supports prepared in Examples 17 to 19 were evaluated. The results are shown in Table 7.

[0062] Table 7 Calcination temperature / ℃ Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 1100 375.1 8.63 0.083 69.17 1300 153.1 15.32 0.163 54.37 1500 140.3 17.54 0.266 46.04 1600 354.8 20.70 0.379 20.14 It can be seen from Table 7 that with the increase of sintering temperature, the pore size and distribution of the support membrane show a trend of first decreasing and then increasing. This may be because the support is not ceramicized enough at 1100°C, the bonding force between ceramic particles is weak, and the gap is large. As the temperature increases to 1500°C, the bonding force between ceramic particles is enhanced, the gap gradually decreases, and the pore size gradually decreases. When the temperature is further increased to 1600°C, grain growth and sintering shrinkage may occur, causing the pore size to increase again. The change trend of the water contact angle is consistent with the pore size distribution and the average pore size. The calcination temperature has a significant effect on the linear shrinkage rate and compressive strength. As the calcination temperature increases, the linear shrinkage rate also increases. This is because the higher the temperature, the higher the degree of ceramicization of the support, the stronger the bonding force between ceramic particles, and the more obvious the grain growth and sintering shrinkage. Therefore, its compressive strength is also significantly enhanced.

[0063] The performance of the bimetallic composite oxide modified ceramic membranes prepared in Example 1 and Examples 20-21 was evaluated. The results are shown in Table 8.

[0064] Table 8 Urea dosage Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 3.0:1 110.3 17.34 0.264 36.44 4.5:1 100.7 17.62 0.260 30.12 6.0:1 123.8 17.57 0.259 33.46 As can be seen from Table 8, the support used in step (2) of Example 1 and Example 20-21 is the same, so the linear shrinkage and compressive strength of the final bimetallic composite oxide modified ceramic membrane do not change much. Urea is used as a precipitant. When decomposed at high temperature, the metal salt can be uniformly precipitated on the surface and inside of the support, and then dried and calcined to form an active coating. The active coating can further modify the pore structure of the support, making its pore size moderate and the distribution more uniform. If the amount of urea added is too little, the reaction is incomplete and the repair effect on the pores is not obvious. If the amount is too much, the reaction rate is faster and the precipitation of the metal salt is more disordered.

[0065] The performance of the bimetallic composite oxide modified ceramic membranes prepared in Example 1 and Examples 22-23 was evaluated. The results are shown in Table 9.

[0066] Table 9 Reaction temperature / ℃ Most probable pore size / nm Linear shrinkage / % Compressive strength / MPa Water contact angle / ° 60 109.3 17.58 0.261 37.77 80 100.7 17.62 0.260 30.12 100 119.3 17.71 0.258 36.67 120 137.6 17.60 0.268 38.29 It can be seen from Table 9 that when the reaction temperature is low, the reaction rate is slow, the reaction process is not thorough, and the membrane pore diameter of the bimetallic composite oxide modified ceramic membrane is slightly larger. However, when the reaction temperature is too high, the reaction is violent, the precipitation process of the metal salt is more disordered, and the membrane pore diameter is unevenly distributed.

[0067] The bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1 were evaluated for their bovine serum albumin filtration performance on a high-pressure flat membrane filtration device. The process was as follows: at room temperature, the main pump speed was 40, and the pressure before the membrane was 0.1 MPa to treat bovine serum albumin with an initial concentration of 1.0 g / L, and the operation was carried out in a circulating filtration mode. The permeate was continuously sampled, and the permeate volume and the bovine serum albumin concentration therein were detected; the results are shown in Figure 3 .Depend on Figure 3 It can be seen that the flux change rate of the bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H is smaller than that of the unmodified ceramic membrane CM-H, indicating that it has better anti-pollution performance. This is because the bimetallic oxide modification can enhance the hydrophilicity of the ceramic membrane, thereby enhancing the repulsion between the membrane surface and pollutants. At the same time, the retention rate of the modified ceramic membrane is greater, indicating that its filtration performance is better than that of the unmodified ceramic membrane.

[0068] The bimetallic composite oxide modified ceramic membrane Mn-Mg / CM-H prepared in Example 1 and the ceramic membrane CM-H prepared in Comparative Example 1 were subjected to coupled catalytic ozonation treatment of bovine serum albumin performance evaluation, wherein the ozone flow rate was 1 L / min, and the results are shown in Figure 4 .Depend on Figure 4 It can be seen that the flux of both membranes decreased rapidly. At 50 min, the J t / J0 values ​​were 10% lower, indicating that both membranes were severely clogged at this time. This is because the degradation of BSA generates a large number of intermediates of different sizes and properties, causing serious membrane fouling. Subsequently, the flux of the modified membrane and the unmodified membrane gradually differed, and the flux of the modified membrane gradually recovered. In the later stage of filtration, the membrane flux of the modified ceramic membrane was greater because the modified membrane had stronger catalytic activity and could mineralize pollutants on its surface and in the pores. This shows that in-situ coupling of modified ceramic membranes with catalytic ozonation is an effective strategy to improve the anti-pollution ability of ceramic membranes.

[0069] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a bimetallic composite oxide modified ceramic membrane, characterized in that: The following steps are involved: S1: Alumina powder, a binder, a pore-forming agent, a flux and an anti-shrinkage agent are mixed, and then the mixture is pressed into a ceramic membrane embryo, and then the ceramic membrane embryo is subjected to gradient temperature rise calcination to obtain a ceramic membrane support body; the gradient temperature rise calcination is: firstly heating to 900°C at a heating rate of 5°C / min, keeping warm for 30min, then heating to 1200°C at a heating rate of 2°C / min, keeping warm for 30min, then heating to 1400-1600°C at a heating rate of 1°C / min, and keeping warm for calcination for 2h; or firstly heating to 900°C at a heating rate of 5°C / min, keeping warm for 30min, then heating to 1150°C at a heating rate of 2°C / min, and keeping warm for calcination for 2h; S2: dissolving a metal salt, urea and polyvinyl pyrrolidone in water to obtain a mixed solution; the metal salt is a mixture of magnesium nitrate and manganese nitrate; S3: Place the ceramic membrane support in the mixed solution, immerse for 4 hours, then bake at 60-120° C. for 4 hours, and then dry and calcine to obtain a bimetallic composite oxide modified ceramic membrane.

2. The preparation method according to claim 1, characterized in that: The mass fraction of the binder in the mixture is 0.5-3%, the mass fraction of the pore former is 0.05-0.5%, the mass fraction of the flux is 0.5-10%, and the mass fraction of the anti-shrinkage agent is 0.5%.

3. The preparation method according to claim 1 or 2, characterized in that: The binder is carboxymethyl cellulose, polyvinyl alcohol or polyvinyl pyrrolidone; the pore-forming agent is ammonium chloride, starch or sodium alginate; the flux is boric acid, calcium oxide or aluminum phosphate; and the anti-shrinkage agent is sodium carbonate.

4. The preparation method according to claim 1, characterized in that: The pressure when the mixture is pressed in S1 is 20t.

5. The preparation method according to claim 1, characterized in that: The mass ratio of magnesium nitrate to manganese nitrate in the metal salt is 2:

1.

6. The preparation method according to claim 5, characterized in that: The molar ratio of urea to metal salt in the mixed solution is 3-6:

1.

7. The preparation method according to claim 6, characterized in that: The concentration of urea in the mixed solution is 0.33 mol / L; the concentration of polyvinyl pyrrolidone is 10 g / L.

8. The preparation method according to claim 1, characterized in that: In S4, the drying is carried out at 105° C. for 2 h; and the calcination is carried out at 550° C. for 2 h.

9. A bimetallic composite oxide modified ceramic membrane obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the bimetallic composite oxide modified ceramic membrane according to claim 9 in bovine serum albumin filtration or catalytic ozonation treatment of bovine serum albumin.

Citation Information

Patent Citations

  • High porosity porous ceramic film supporting body and preparation method thereof

    CN108117379A